DESIGN AND PERFORMANCE ANALYSIS OF HORIZONTAL AXIS WIND TURBINE TAPERLESS NACA 6510 USING QBLADE SOFTWARE - Fanisya Dwiyani; Ahmad Zamakhsyari Sidiq; Ahmad Said (JEMIS (Journal of Engineering & Management in Industrial System), 2022)
The crisis of non-renewable energy resources has pushed the global community to overcome the dominance of fossil fuel power plants. The utilization of new renewable energy sources is a solution because it is considered to have energy sources that will continue to be renewed, including wind energy. Since ancient times, wind energy can be harvested and converted into electrical energy using wind turbines. This research was conducted to analyze the feasibility of the design performance of the horizontal axis wind turbine blade NACA airfoil 6510. The feasibility analysis of the performance can be known from the simulation results by referring to the resulting efficiency value. The analysis was carried out by studying literature to determine the characteristics of the NACA airfoil 6510 and performance simulation using Qblade software. The design is carried out using data on the average maximum wind speed in Indonesia of 12 m/s. Therefore, the results of the feasibility of wind turbine blade design performance with NACA airfoil 6510 have an efficiency of 44%.